Outcomes of Primary Percutaneous Coronary Intervention in Patients with a Thrombolysis in Myocardial Infarction Score of Five or Higher - Naveed Iqbal, Zain Mehmood Butt, Mashooque Ali Dasti, Faraz Farooq Memon, Atif Ahmed Khan, Syed Nadeem Hassan Rizvi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the rate of adverse outcome in patients with at least five TIMI scores after primary percutaneous coronary intervention. Methods: We conducted this descriptive study at National Institute of Cardiovascular Diseases Karachi for six months. This study included 200 men and women with chest pain who presented to the emergency department with chest pain and ST-segment elevation myocardial infarction. PCI processes were executed by cardiologists, and any post-procedure adverse outcomes were noted throughout the hospital stay. Results: A total of 200 participants were involved, 167 (83.5%) being males, and 33 (16.5%) being females. There were 95 (47.5%) moderate risk cases and 105 (52.5%) high-risk cases based on the TIMI scores. In the survey of patient outcomes, death occurred in 18.5% of cases, heart failure was observed in 43 cases (21.5%), cardiogenic shock was observed in 27 cases (13.5%), and ventricular arrhythmia was observed in 44 (22%) cases. Practical Implication: This research on the outcomes of primary PCI in patients with a TIMI score of five or higher can provide valuable information for healthcare providers, leading to improved patient selection, enhanced treatment decision-making, tailored interventions, reduced morbidity and mortality rates, and increased cost-effectiveness in managing myocardial infarction cases. These practical implications can significantly benefit the community by improving patient outcomes and optimizing healthcare resource utilization. Conclusion: A TIMI risk score of five or higher can also identify patients who may have heart failure, cardiogenic shock, and ventricular arrhythmias. Keywords: Primaryipercutaneous coronary intervention, thrombolysis, myocardial infarction, score of five or higher